Oxygen Functionalization of Hexagonal Boron Nitride on Ni(111). Issue 37 (5th June 2019) - Späth, Florian; Soni, Himadri R.; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Phillip; Hieringer, Wolfgang; Görling, Andreas; Steinrück, Hans‐Peter; Papp, Christian
Abstract: The interaction of single‐layer hexagonal boron nitride (h‐BN) on Ni(111) with molecular oxygen from a supersonic molecular beam led to a covalently bonded molecular oxygen species, which was identified as being between a superoxide and a peroxide. This is a rare example of an activated adsorption process leading to a molecular adsorbate. The amount of oxygen functionalization depended on the kinetic energy of the molecular beam. For a kinetic energy of 0.7 eV, an oxygen coverage of 0.4 ML was found. Near‐edge X‐ray adsorption fine structure (NEXAFS) spectroscopy revealed a stronger bond of h‐BN to the Ni(111) substrate in the presence of the covalently bound oxygen species. Oxygen adsorption also led to a shift of the valence bands to lower binding energies. Subsequent temperature‐programmed X‐ray photoelectron spectroscopy revealed that the oxygen boron bonds are stable up to approximately 580 K, when desorption, and simultaneously, etching of h‐BN set in. The experimental results were substantiated by density functional theory calculations, which provided insight to the adsorption geometry, the adsorption energy and the reaction pathway. Abstract : Activated adsorption : The interaction of single‐layer hexagonal boron nitride (h‐BN) on Ni(111) with molecular oxygen from a supersonic molecular beam led to a covalently bonded molecular oxygen species, which was identified as being between a superoxide and a peroxide species. This is a rare example of an activated adsorption process leading to a molecular adsorbate.